Philo's influence on Valentinian tradition - Auvinen, Risto (Studia Philonica monographs, 2024)
"In this book Risto Auvinen reevalutes the relationship between the exegetical and philosophical traditions found in the works of Philo and those of the Valentinian gnostic tradition, with a particular focus on the latter half of the second century, Valentinianism's formative years. Texts examined include fragments of Valentinus, Heracleon, and Ptolemy's Letter to Flora, in addition to the Valentinian source included in the Excerpta ex Theodoto by Clement of Alexandria and related sections in Irenaeus's Adversus haereses. Auvinen asserts that the number of parallels with Philo in the Valentinian sources increases the likelihood that there was a historical relationship between Philo's writings and Valentinian teachers. These connections expand our knowledge not only of the preservation and circulation of Philo's texts in the latter part of the second century but also of the importance of the allegorical traditions of Hellenistic Judaism on Valentinus's school of thought and on Gnosticism more broadly."--Publisher